2019
DOI: 10.1159/000499633
|View full text |Cite
|
Sign up to set email alerts
|

Augmented Adsorptive Blood Purification during Continuous Veno-Venous Haemodiafiltration in a Severe Septic, Acute Kidney Injury Patient: Use of oXiris®: A Single Centre Case Report

Abstract: The use of the oXiris® haemofilter during continuous veno-venous haemodiafiltration (CVVHDF) for acute kidney injury (AKI) and severe sepsis is not completely understood. Although this filter has in vitro adsorptive properties for blood-borne cytokines and other humoural mediators of sepsis, its clinical usefulness is uncertain. Given its inherent adsorptive limitation for septic mediators, we developed a CVVHDF protocol in which the oXiris haemofilter was electively changed every 12 h even though there was no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 12 publications
3
12
0
1
Order By: Relevance
“…In this study, we observed a significant improvement of hemodynamics among hemodynamically instable patients after Oxiris‐CRRT, which has already been widely confirmed by domestic and foreign researchers 13,14,16‐18 . However, the mechanism remains unclear.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…In this study, we observed a significant improvement of hemodynamics among hemodynamically instable patients after Oxiris‐CRRT, which has already been widely confirmed by domestic and foreign researchers 13,14,16‐18 . However, the mechanism remains unclear.…”
Section: Discussionsupporting
confidence: 69%
“…In this study, we observed a significant improvement of hemodynamics among hemodynamically instable patients after Oxiris-CRRT, which has already been widely confirmed by domestic and foreign researchers. 13,14,[16][17][18] However, the mechanism remains unclear. Researchers have found that the main manifestations of microcirculation disorder were leukocyte adhesion and plasma extravasation, which may explain the possible mechanism of shock in sepsis patients; namely, plasma extravasation caused a decrease in the effective circulation capacity.…”
Section: Discussionmentioning
confidence: 99%
“…In another recent case report, a critically ill patient with severe sepsis secondary to a Gram-negative bacterial infection and sepsis-associated AKI was treated with CVVHDF using the oXiris set electively changed every 12 h for 3 consecutive days. The patient, who required high-dose vasopressor support and mechanical ventilation, showed reduction in the need for vasopressor support-by day 4, vasopressor requirements ceased and extubation occurred [94]. Similar findings were documented in a French study involving 31 septic patients receiving oXiris-based CRRT between 2014 and 2019.…”
Section: Prescription In Sepsissupporting
confidence: 77%
“…Certain filter membranes putatively aid immunoadsorption of cytokines. 15,16 It is unknown whether these would be beneficial in patients with COVID-19, and their use should be reserved for specific indications or clinical trials.…”
Section: Conventional Ckrt Fluidsmentioning
confidence: 99%